Behaviour of a discontinuity at the wave-head propagating through a relaxing gas - Sharma J.; Shyam R.; Sharma V.D. (My University, 2025)
The rate of amplification of a discontinuity in the velocity gradient is evaluated at the wave-head in a spatially uniform but time evolving flow of a relaxing gas. The paper investigates the effects of relaxation (present in the flow) and the initial wave front curvature on the growth and decay behaviour of waves in the thermodynamical state of weak or strong equilibrium. © 1982 Springer-Verlag.